Clinician perspectives on using pharmacogenomics in clinical practice. (August 2015) - Unertl, Kim M; Field, Julie R; Price, Lisa; Peterson, Josh F
Aim : To describe the knowledge and attitudes of clinicians participating in a large pharmacogenomics implementation program.Materials & methods : Semi-structured interviews with 15 physicians and nurse practitioners were conducted.Results : Three categories of themes were identified: preparation and knowledge, pharmacogenomics usage in practice, and future management of genomic variants. Providers expressed an inability to keep up with the rapid pace of evidence generation and indicated strong support for clinical decision support to assist with genotype-tailored therapies. Concerns raised by clinicians included effectively communicating results, long-term responsibility for actionable results and handoffs with providers outside the implementation program.Conclusion : Clinicians identified their own knowledge deficits, workflow integration and longitudinal responsibility as challenges to successful usage of pharmacogenomics in clinical practice.